Evaluation of the Effectiveness of “Electron Go out Mosquito Small Lamp” in Disease Vector Mosquito Control Benin West Africa - Tokponnon, Tatchémè Filémon (My University, 2023)
In the context of mosquito control, a plethora of devices have been put on the market. The effectiveness of these devices is not always proven, but some have interesting principles that have the potential to be a good means of mosquito control. Among these interesting devices are the photonic traps. We have carried out nightly captures of mosquitoes on human baits in the presence and absence of the device. These captures were made during the rainy season in the localities of Zogbadjè and Mènontin. The captures were made under the same atmospheric conditions at the same locations at 5-day intervals. These captures were made twice per house, indoors and outdoors, with one blank capture without the device and one capture with the device. The captured mosquitoes were identified and classified by genus and their aggressiveness determined by calculating the biting rate. A total of 845 mosquitoes were captured during these captures with 296 mosquitoes captured indoors without the device and 132 mosquitoes with the device present. This represents a decrease of 55.40% in culicidae density. Furthermore, a significant decrease was observed in aggressiveness, from 49 to 22 bites per man per night (b/m/n) with the use of the device. This decrease is even more important for nocturnal species such as Anopheles spp. whose aggressiveness decreased by 90%. The present study confirms the effectiveness of the “Electron go out mosquito small lamp” in reducing Culicidae density and mosquito aggression even in the presence of chemotactic interference. However, this study was limited in time and focused only on the ability of the device to reduce mosquito numbers and did not assess its epidemiological efficacy. It is therefore important to extend the work to examine the influence of the use of this device on population health and the occurrence of mosquito-borne diseases, particularly malaria.
Keywords: Mosquito Control; Electron Go Out Mosquito; Effectiveness; Culicidae; Density; Phototactism Bénin